2012
DOI: 10.1136/jmedgenet-2012-101002
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of recurrent duplications of the DiGeorge syndrome region on both chromosome 22 homologues due to inherited and de novo events

Abstract: Our studies that reveal phenotypic variability in patients with four copies of the 22q11.2 genomic segment, demonstrate that both inherited and de novo events can result in the generation of homozygous duplications, and further document how multiple seemingly rare events can occur in a single individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…There are several possible explanations for the incomplete penetrance and variable expressivity observed in this syndrome: (1) the variable size of the imbalance (as we saw above); (2) the influence of several interfering genes or epigenetic factors; and (3) the co‐existence of additional CNVs …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There are several possible explanations for the incomplete penetrance and variable expressivity observed in this syndrome: (1) the variable size of the imbalance (as we saw above); (2) the influence of several interfering genes or epigenetic factors; and (3) the co‐existence of additional CNVs …”
Section: Discussionmentioning
confidence: 90%
“…Transgenic mice overexpressing human TBX1 with a gain‐of‐function mutation had the same phenotype as with 22q11.2 deletion . Genetic studies in mice have suggested the presence of modifier genes both in the critical region and elsewhere in the genome . Most of these candidate genes are likely be involved in TBX1 –related pathways in the development of the pharyngeal germ layers.…”
Section: Discussionmentioning
confidence: 91%
“…Biallelic CNVs can cause disease either as homozygous deletions in consanguineous populations or as compound heterozygous deletions (Figure A‐B). Rarely, common DNA rearrangements, each of which independently leads to disease, can aggregate in trans at a single locus or can be seen in homozygous state due to inherited and/or de novo events …”
Section: Downstream Mechanisms: From Cnv To Phenotype and Beyondmentioning
confidence: 99%
“…We also identified one homozygous deletion of CHRNA7 in 15q13.3, one homozygous deletion of NPHP1 in 2q13, 24 hemizygous deletions of STS in Xp22.31, four homozygous duplications (or triplications) of NPHP1 in 2q13, one homozygous duplication (or triplication) of BP1/BP2 in 15q11.2, two homozygous duplications (or triplications) of CHRNA7 in 15q13.3, three homozygous duplications of the DiGeorge/velocardiofacial syndrome (DGS/VCFS) region in 22q11.21 (Bi et al 2012), and one Prader-Willi/Angelman syndromes (PWS/AS) interstitial triplication in 15q11.2q13.…”
Section: Prevalence Of the Known Pathogenic Recurrent Regionsmentioning
confidence: 99%